Social Inequalities in Participation in Cervical Cancer Screening in a Metropolitan Area Implementing a Pilot Organised Screening Programme (Paris Region, France) - Céline Audiger; Céline Audiger; Thomas Bovagnet; Julia Bardes; Gaëlle Abihsera; Jérôme Nicolet; Michel Deghaye; Audrey Bochaton; Gwenn Menvielle (Frontiers Media S.A., 2022)
Objectives: We aimed to examine social inequalities in participation in cervical cancer screening (CCS) in a metropolitan area by implementing a pilot organised screening programme. The pilot programme consisted of sending invitations to women who did not perform a pap smear within the past 3 years, managing interventions to reach vulnerable women, training healthcare professionals, and organising follow-ups of abnormal pap smears.Methods: We studied participation in CCS between January 2014 and December 2016 among 241,257 women aged 25-63 years old. To assess relative inequalities, Odds Ratios were computed using multilevel logistic regression. To assess absolute inequalities, the CCS coverage and the rate difference were calculated. Inequalities were computed by age and neighbourhood characteristics (social deprivation and proportion of single women).Results: Disparities in participation in CCS were observed by age and social deprivation. For overall screening compared to opportunistic screening, disparities by age were larger (OR25-35_vs._55-64 = 2.13 [2.08-2.19] compared to 2.02 [1.96-2.07]), but disparities by social deprivation were decreased (OR10%_most_vs._10%_least_deprived = 2.09 [1.90-2.30] compared to 2.22 [2.02-2.44]).Conclusion: Disparities in CCS participation remain despite the organised programme. To reduce these inequalities, free screening should be proposed and evaluated.